# Find the sum of thuis question

posted by
**Mandy**
.

Can someone find the sum for this equation please.

(X^2)/(X^2-16)=(5X+4)/(X^2-16)

I don't think it is finding the sum, but I can simplify the equation.

(X^2)/(X^2-16)=(5X+4)/(X^2-16)

First, multiply both sides by X^-16.

X^2 = 5X+4

Subtract 5X+4 from both sides.

X^2-5X-4 = 0

However, this equation cannot be factored. If the original equation was

(X^2)/(X^2-16)=(5X**-**4)/(X^2-16)

Then it would simplfy to

X^2-5X+4 = 0

Which could be factored into

(X-1)(X-4) = 0

I hope this helps. Thanks for asking.